Spiritual abuse under the banner of the right to freedom of religion in religious cults can be addressed - S. P. Pretorius (Acta Theologica)
The international endeavour to afford the right to freedom of religion to all world citizens is essential. This right ensures that people can choose their own religion and freely participate in the practice thereof. Although the conventions on religious freedom prohibit the use of unethical coercion in order to proselytise and retain members, the enforcement of this prohibition is problematic. Underlying psychological processes that induce members in cults to engage in radical behaviour changes cannot be proved without reasonable doubt in any legal action. The conclusion reached in this article is that although – on paper – the right to religious freedom ensures freedom in the sense that people can choose their religion, it cannot ensure that worship in any religion is a voluntary act on the part of the participants. On the one hand, religious freedom has opened the world of religion to people; but at the same time, it has also created a vague, or “grey” area where abuse can flourish under the banner of so-called “freedom”. Freedom that is not clearly defined can lead to anarchism. Abuse in religious cults can be addressed by cultivating public awareness through the gathering and distribution of information on the abusive practices of these groups.